Biological Effects of Indigenous Entomopathogenic Fungi and Their Application Methods on Spodoptera frugiperda - Minarni, Endang Warih; Nurtiati, Nurtiati; Istiqomah, Dina (Jurnal Perlindungan Tanaman Indonesia, 2022)
Spodoptera frugiperda is a new pest in Indonesia that attacks corn and can cause up to 100 percent damageon young plants. As an invasive pest, information on potential indigenous natural enemies that cancontrol this pest is needed. This study aims to determine the effectiveness of indigenous entomopathogenic fungi and their application methods on mortality, feeding activity, growth, fecundity, and fertility of S. frugiperda. This study used a factorial Completely Randomized Block Design (RCBD) method consisting of 10 treatments. Treatmentstested werecombination of fungi species, namely Fusarium sp., Aspergillus oryzae, Entomophthora sp. with conidia density 109 ml-1, distilled water and cypermethrin at concentration of 1 ml.L-1 as a control. Two application techniques used were direct application on S. frugiperda larvae and diet test. Each treatment was repeated three times resulting in30 experimental units. Variables observed included mortality, feeding activity, growth, fecundity, and fertility of S. frugiperda. Results showed that the three fungi and cypermethrin treatment did not cause mortality, but reduced feeding activity, fecundity and fertility of S. frugiperda. Application of entomopathogenic fungi ondietswas more effective than directly spraying S. frugiperda larvae. The best treatment combination that suppressed feeding activity was the application of Aspergillus oryzae sprayed on S. frugiperda diet.It was also suspected that S. frugiperda larvae used in this test had developed resistance to cypermethrin.